Praktik Sikap Toleransi Umat Beragama di Kampung Adat Desa Bajulan Kabupaten Nganjuk - Jelli, Arum (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study is first to describe the practice of religious tolerance among religious communities in the Bajulan Village Traditional Village, Nganjuk Regency and second to describe the factors that encourage tolerance. Using a qualitative method with a phenomenological approach. Data collection techniques include observation, interviews, and documentation. With informants namely the Bajulan village government, religious leaders and followers of Islam, Christianity and Hinduism. The findings show that the attitude of tolerance is an important part of the daily life of the community and the traditional village provides a good space to grow and maintain an attitude of mutual respect and respect without forcing beliefs, seen from the social activities of its residents who are free to choose and carry out religious activities from the small family circle to the community circle, participating in maintaining and helping each other between religious communities such as the value of local wisdom of mutual cooperation, community service, construction of places of worship, village cleaning, sadranan or sowan punden. Interfaith dialogues are carried out on various occasions for example after the Nyepi celebration and the Pura piodalan, religious moderation camps. Driving factors, First, individual self-awareness of wanting to live in peace, harmony, and harmony. Second, all religious teachings teach the goodness of compassion and mutual respect. The practice of religious tolerance in the traditional village of Bajulan village reflects the real application of Bhikhu Parekh’s theory, the community is able to bridge religious differences with dialogue, local wisdom traditions and strong self-awareness, peaceful coexistence is built on the basis of recognition, appreciation and equality in diversity.